PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN TRANSFER PRICING TERHADAP PENGHINDARAN PAJAK - Alda Noervirachma (Yayasan Kayyis Mulia Jaya, 2026)
This study aims to determine and demonstrate the effect of company size, sales growth, and transfer pricing on tax avoidance in consumer non-cyclical companies listed on the Indonesia Stock Exchange from 2019 to 2024. Purposive sampling was used to select 11 companies listed on the IDX. Data analysis used multiple linear regression analysis, processed and processed using Eviews 12 software. The results indicate that company size partially influences tax avoidance; sales growth has no effect on tax avoidance, and transfer pricing does. Simultaneously, company size, sales growth, and transfer pricing significantly influence tax avoidance. Keywords: Company Size, Sales Growth, Transfer Pricing, and Tax Avoidance.